Abundance of phytoplankton in the Kampar Kiri River, Mentulik Village, Kampar Kiri Sub-District, Kampar District, Riau Province - Lubis, Rizki Anita; Sumiarsih, Eni; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Kampar Kiri River is located in Riau, there are fisheries and domestic activities that potential in affecting water quality. To understand the abundance of phytoplankton present in that river, a study has been conducted in July 2016. Samplings were conducted 3 times, once week, in 3 stations. Results shown that there are 11 species of phytoplankton present in the river. They were classified into three classes, `namely: Bacillariophyceae (4 species), Chloropyhceae (3 species) and Cyanophyceae (4 species). The average of phytoplankton abundance was around 359 – 1,392 cells/L. While the water quality parameters are as follows: temperature: 30 - 310C, transparency: 15.6 – 22.6 cm, pH: 6, DO: 3.8 - 4.1 mg/L, nitrate: 0.05 - 0.11 mg/L and phosphate: 0.19 - 0.23 mg/L. Based on the composition of pyhtoplankton, it can be concluded that the Kampar Kiri River water can be categorized as low.Keyword : Phytoplankton, Kampar Kiri River, Water Quality,